ANTIOXIDANT ACTIVITY, TOTAL PHENOLIC, AND FLAVONOID CONTENTS OF THE EXTRACT OF ENDOPHYTIC FUNGI DERIVED FROM TURMERIC (Curcuma longa) LEAVES - Eris Septiana; Siti Irma Rahmawati; Fauzia Nurul Izzati; Partomuan Simanjuntak (Sanata Dharma University, 2019)
Air pollution can increase free radicals that may worsen some diseases. Antioxidants such as phenol and flavonoid compounds are known to counteract these free radicals. Long term use of synthetic antioxidants is known to cause bad effects on the body. Therefore, the necessity to search for natural antioxidants from plants and its endophytic microbes continues with the hope to obtain potential natural antioxidants with minimum side effects. The purpose of this study was to determine the antioxidant activity, total phenolic, and flavonoid contents of the extract of endophytic fungi which were derived from the Bogor-originated turmeric leaves via in vitro isolation. DPPH free radical scavenging method was used to determine in vitro antioxidant activity. The total phenolic and flavonoid contents assays were based on the Follin-Ciocalteu and aluminium chloride reagents, respectively. The extract of endophytic fungi of Bo.Ci.Cl.D1 and Bo.Ci.Cl.D2 showed antioxidant activity with IC50 value at 24.04 and 96.08 mg/L, respectively. Total phenolic content of Bo.Ci.Cl.D1 and Bo.Ci.Cl.D2 extracts were 113.47 and 81.83 mg gallic acid equivalent/g extract respectively. Total flavonoid content of Bo.Cl.D1 and Bo.Ci.Cl.D2 extracts were 41.79 and 38.50 mg quercetin equivalent/g extract, respectively. Based on these assays, it could be concluded that the extract of Bo.Ci.Cl.D1 has better antioxidant activities than Bo.Ci.Cl.D2.